Weathering Cash Flow Shocks - BROWN, JAMES R.; GUSTAFSON, MATTHEW T.; IVANOV, IVAN T. (Journal of Finance, 2021)
ABSTRACT Unexpectedly severe winter weather, which is arguably exogenous to firm and bank fundamentals, represents a significant cash flow shock for bank‐borrowing firms. Firms respond to these shocks by drawing on and increasing the size of their credit lines. Banks charge borrowers for this liquidity via increased interest rates and less borrower‐friendly loan provisions. Credit line adjustments occur within one calendar quarter of the shock and persist for at least nine months. Overall, we provide evidence that bank credit lines are an important tool for managing the nonfundamental component of cash flow volatility, especially for solvent, small bank borrowers.